2020
DOI: 10.1016/j.heliyon.2020.e03849
|View full text |Cite
|
Sign up to set email alerts
|

Maternal profiles and social determinants of severe acute malnutrition among children under-five years of age: A case-control study in Nepal

Abstract: Background: Addressing the determinants of severe acute malnutrition (SAM) among children remains a challenge in Nepal. This study investigated the effect of maternal and social determinants of SAM among under-five children of Nepal. Methods: We conducted a hospital-based unmatched case-control study with 256 under-five children (128 cases and 128 controls). The children aged 6-59 months were taken, and the cases and controls were defined based on mid-upper arm circumference (MUAC). Results: Backward Stepwise … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
24
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(41 citation statements)
references
References 25 publications
9
24
0
2
Order By: Relevance
“…In this study we found that children were more acute malnutrition suffers who came from low income family having no hygienic latrine facilities. Similar results were found in other studies in Nepal [ 52 ], Ethiopia [ 53 ], Nigeria [ 54 ], they found that poverty one of the crucial factors for malnutrition among under-five children.…”
Section: Discussionsupporting
confidence: 91%
“…In this study we found that children were more acute malnutrition suffers who came from low income family having no hygienic latrine facilities. Similar results were found in other studies in Nepal [ 52 ], Ethiopia [ 53 ], Nigeria [ 54 ], they found that poverty one of the crucial factors for malnutrition among under-five children.…”
Section: Discussionsupporting
confidence: 91%
“…Data have shown that breastfeeding has cognitive and health benefits for both the child and their mother (Hossain et al, 2020;Imran et al, 2019). Exclusive breastfeeding during the first 6 months of life reduces the risk of ARI in infants.…”
Section: Discussionmentioning
confidence: 99%
“…Knowledge of social determinants (SDs) can contribute to implementing comprehensive social programs to address the conditions that generate disadvantages to people's health [2]. For example, unfavorable socio-economic conditions are one SD that show greater consistency and persistence over time [3][4][5]. Furthermore, age [6], gender [3], and demographic and ethnic conditions [2,7] are usually relevant, among others.…”
Section: Introductionmentioning
confidence: 99%